2019
DOI: 10.1093/hmg/ddz290
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate rapidly decreases hepatic lipid and glycogen storage in neonatal mice with glycogen storage disease type Ia

Abstract: Glycogen storage disease type Ia (GSD Ia) is caused by autosomal mutations in glucose-6-phosphatase α catalytic subunit (G6PC) and can present with severe hypoglycemia, lactic acidosis and hypertriglyceridemia. In both children and adults with GSD Ia, there is over-accumulation of hepatic glycogen and triglycerides that can lead to steatohepatitis and a risk for hepatocellular adenoma or carcinoma. Here, we examined the effects of the commonly used peroxisomal proliferated activated receptor α agonist, fenofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…There are some data suggesting that treatment with FN may have various effects on autophagy in hepatocytes. In neonate, 5-day-old G6pc -/mice (autosomal mutation in glucose-6-phosphatase; a model of neonatal glycogen storage disease type Ia) 5day-long treatment with FN induced autophagy in the liver accompanied by increased hepatic LC3-II and beclin 1 protein expression, and TEM analyses revealed numerous autophagosomes with electron-dense glycogen granules [14]. In hepatocytes isolated from 8week-old male C57BL/6J mice treated with FN (0.5-5 µg/ml for 24 hours), the drug exerted a protective effect against acetaminophen (APAP)-induced hepatotoxicity by enhancing autophagy via elevation of LC3-II and degradation of p62 proteins [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some data suggesting that treatment with FN may have various effects on autophagy in hepatocytes. In neonate, 5-day-old G6pc -/mice (autosomal mutation in glucose-6-phosphatase; a model of neonatal glycogen storage disease type Ia) 5day-long treatment with FN induced autophagy in the liver accompanied by increased hepatic LC3-II and beclin 1 protein expression, and TEM analyses revealed numerous autophagosomes with electron-dense glycogen granules [14]. In hepatocytes isolated from 8week-old male C57BL/6J mice treated with FN (0.5-5 µg/ml for 24 hours), the drug exerted a protective effect against acetaminophen (APAP)-induced hepatotoxicity by enhancing autophagy via elevation of LC3-II and degradation of p62 proteins [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the present study we decided to compare FN's effects on hepatocytes' ultrastructure in young and old healthy Wistar-Han rats, and on the expression of autophagyrelated proteins, i.e. LC3A/B which is related to autophagosome formation, and beclin 1, a common regulator of autophagy and apoptosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…VK2809 is highly liver-specific and is rapidly eliminated in the bile [111] . VK2809 reduced hepatosteatosis in mouse models of NAFLD [112] and glycogen storage disease type Ia (GSD-Ia), an inherited metabolic liver disease that can develop many similar hepatic features as NAFLD [33] . In the mouse model of GSD1a, VK2809 treatment decreased hepatic lipid content through its simultaneous restoration of autophagy, mitochondrial biogenesis, and β-oxidation of fatty acids [33] .…”
Section: Clinical Trials Of T 4 and Thyromemetics In Patients With Nafld/nashmentioning
confidence: 99%
“…This study showed that PPARα activation prevents triglyceride accumulation in NASH by increasing fatty acid turnover and catabolism via induction of acyl-CoA oxidase, liver fatty acid binding protein, L-bifunctional enzyme, and peroxisomal ketothiolase gene expression [70]. Similarly, in a rodent G6Pase model of the glycogen storage disease, GSD1a, in which patients developed NASH and cirrhosis, the PPARα mixed agonist, bezafibrate, or selective PPARα agonist, fenefibrate, decreased hepatic triglycerides and increased β-oxidation of fatty acids with a concomitant increase in autophagy [71,72].…”
Section: Implication Of Pparα-lysosomal Crosstalk In Nafldmentioning
confidence: 99%